Faktor yang Berhubungan dengan Penggunaan Intra Uterine Device (IUD) di Pusat Pelayanan Keluarga Sejahtera (Pusyan Gatra) Tahun 2016 - Sarah Christiawan; Windhu Purnomo (Universitas Airlangga, 2017)
The rate of growth population (LPP) becomes the main problem that is being faced by Indonesia today, one of them was East Java Province which increased 0.06 in 2000–2010 from 1990–2000 period. One effort to control LPP was family planning program by using contraception, especially Intra Uterine Device (IUD) to regulate the distance of pregnancy and to regulate birth spacing. Achievements of new Long Term Contraception Method (MKJP) acceptors especially IUD tend to decrease from 2013 to 2015 in Surabaya. The achievement of the proportion of new IUD acceptors in 2016 in Pusyan Gatra decreased by 6% became 34% from 2015 which is 40%. This study aimed to know and analyze the variables associated with the use of IUD in Pusyan Gatra in 2016 by using chi-square test. This research was an analytic quantitative research with cross-sectional design. This research data source were a new acceptor secondary data of MKJP in 2016. Population in this research were 270 new acceptors of MKJP from January to December 2016. The independent variables were age, educational level, employment status, and parity. The results from chi – square test were age (p = 0.002) and parity (p = 0.001) which related to IUD. Level of education and employment status of acceptors had no significant relationship with IUD in Pusyan Gatra. Therefore, the couple of reproductive (PUS) were >35 years old who had parity >2 and not using long–term contraception method yet, the counseling about using MKJP such as IUD must be improved.